Effect of Hydrocarbon-Polluted Seawater on the Cell Density of Microalgae Scenedesmus vacuolatus Shihira & Krauss - Clara Alverina Santoso; Noverita Dian Takarina; Hanies Ambarsari; Nining Betawati Prihantini; Sitaresmi (Microbiology Indonesia, 2020)
Study about the effect of hydrocarbon-polluted seawater on the cell density of microalgae Scenedesmus vacuolatus has been done. Hydrocarbon pollution derived from oil in the sea can inhibit photosynthesis process of microalgaes. This might impact the density of microalgae cells. The purposes of this study are to determine the effect of the concentration of hydrocarbon-polluted seawater on the density of Scenedesmus vacuolatus microalgae cells and to determine the optimum treatment to reduce total petroleum hydrocarbons (TPH) levels. Sampling of hydrocarbon-polluted seawater was taken at Kali Adem port, Jakarta. The treatment done in this research used Walne medium with the addition of 25% hydrocarbon-polluted seawater (A), 50% (B), 75% (C), and 100% (D). Control is Walne medium with sterile seawater that was not from the Kali Adem port. The results showed the highest average density of Scenedesmus vacuolatus cells was in the control sample. This can be seen from the results of the average cell density at peak time of 29.48 x 105 cells / mL, as well as the log phase length of Scenedesmus vacuolatus. Measurement of TPH levels showed decreases of TPH in all treatments. The optimum treatment to reduce TPH levels is on treatment B with reduction percentage of 70.62%. Key words: Kali Adem port, Scenedesmus vacuolatus, total petroleum hydrocarbon (TPH), Walne medium